1984
DOI: 10.1002/art.1780270805
|View full text |Cite
|
Sign up to set email alerts
|

Severe functional declines, work disability, and increased mortality in seventy‐five rheumatoid arthritis patients studied over nine years

Abstract: Seventy-five patients with rheumatoid arthritis (RA) were reviewed 9 years after an extensive evaluation which included quantitative measures of functional capacity. These patients had received multiple intraarticular injections of thiotepa with corticosteroids early in their course, but appear demographically and functionally similar to other RA patients who had not received this therapy. Severe morbidity was seen over the 9-year period in the 55 surviving patients, including significantly lower overall funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
284
2
21

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 660 publications
(323 citation statements)
references
References 29 publications
9
284
2
21
Order By: Relevance
“…It is associated with substantial morbidity and mortality (2,3). Because many of the adverse events associated with RA, such as opportunistic infections and cancer, are relatively rare and because all of them are potentially related to medication use, the study of RA-related comorbidities requires large numbers of patients with detailed information about medication use.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with substantial morbidity and mortality (2,3). Because many of the adverse events associated with RA, such as opportunistic infections and cancer, are relatively rare and because all of them are potentially related to medication use, the study of RA-related comorbidities requires large numbers of patients with detailed information about medication use.…”
Section: Introductionmentioning
confidence: 99%
“…However, joint damage accumulation is highly variable, differing up to 10-fold between individuals after 8-12 years of disease (3,4). The mechanisms that produce these widely varying results are as yet poorly defined in humans.…”
mentioning
confidence: 99%
“…This change in treatment philosophy was not based on direct comparisons of the efficacy of these strategies, but rather was motivated by the recognition that joint damage occurs early in RA, that the health outcomes of patients treated using the previous strategy were generally poor, and that diseasemodifying medications were safer than previously thought (5)(6)(7)(8)(9)(10). Recently, the findings from several short-term controlled trials and observational studies have suggested that treatment with disease-modifying medications initiated early in the course of RA leads to improved control of joint inflammation, less joint damage, and better health compared with the outcomes following even short delays in treatment (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%